2018
DOI: 10.1002/ijc.31637
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study of HPV prevalence and detection of CIN2+ in vaginal self‐sampling compared to cervical specimens collected by medical personnel

Abstract: We conducted a randomised study to compare vaginal self-sampling with assisted sampling by medical personnel on the cervix for HPV testing in primary screening. The first aim was to determine if the HPV prevalence is independent of sampling location (vagina versus cervix) and the person performing the sampling. The second aim was to evaluate if the two sampling strategies differed in the detection rate of CIN2+. In total, 19,523 women were randomised into two groups, with 9926 invited to perform self-sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
17
1
Order By: Relevance
“…HPV testing using vaginal self-sampling on FTA card has been shown to be as reliable as assisted cervical sampling [14, 15]. We have recently shown that repeating the self-sampling and HPV test for women that were HPV positive in the screening sample after 4–6 months, in order to identify women with persistent infections, can results in more than two-fold higher detection rate of CIN2 + -lesions, compared to cytology screening [14, 15]. This method could decrease both incidence and mortality in cervical cancer, as early detection and treatment remains the most effective means of prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV testing using vaginal self-sampling on FTA card has been shown to be as reliable as assisted cervical sampling [14, 15]. We have recently shown that repeating the self-sampling and HPV test for women that were HPV positive in the screening sample after 4–6 months, in order to identify women with persistent infections, can results in more than two-fold higher detection rate of CIN2 + -lesions, compared to cytology screening [14, 15]. This method could decrease both incidence and mortality in cervical cancer, as early detection and treatment remains the most effective means of prevention.…”
Section: Discussionmentioning
confidence: 99%
“…HPVIR is a laboratory developed (LDT), multiplex real-time PCR test, detecting and quantifying HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58 and 59 [11]. In this application, a cervical or vaginal sample is applied on an indicating FTA elute micro card™ [1215] and left to dry before storage. The clinical material applied to this card is stable at room temperature and samples stored on FTA cards for 1 year have shown identical HPV typing results as compared to the use of liquid-based cytology (LBC) collection media [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data was derived from women between 30 and 60 years of age participating in two randomized intervention studies that were conducted in Uppsala County, Sweden, between 2013 and 2015 [3, 23]. The first randomized study included women between 30 and 49 years of age and had as aim to compare the detection rate of CIN2+ lesions based on histology in women performing repeated self-sampling of vaginal fluid for hrHPV testing with women following the regular screening program based on Pap smear cytology [3].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, recent studies have reported that self-sampling HPV testing is a useful approach to increasing the participation rate [32]. Also, the sensitivity and speci city of self-sampling HPV testing are nearly equal to those of a clinician performing the HPV testing [32][33][34]. Some countries have already introduced self-sampling HPV testing for non-attenders [35,37].…”
Section: Consent Publicationmentioning
confidence: 99%